Some simplest integral equalities equivalent to the Riemann hypothesis - Sekatskii, S. K.; Beltraminelli, S. (Ukrains’kyi Matematychnyi Zhurnal, 2022)
UDC 511.3We show that the following integral equalities are equivalent to the Riemann hypothesis for any real $a>0$ and any real $0